1998
DOI: 10.1016/s0092-8674(00)81706-7
|View full text |Cite
|
Sign up to set email alerts
|

A VSG Expression Site–Associated Gene Confers Resistance to Human Serum in Trypanosoma rhodesiense

Abstract: Infectivity of Trypanosoma brucei rhodesiense to humans is due to its resistance to a lytic factor present in human serum. In the ETat 1 strain this character was associated with antigenic variation, since expression of the ETat 1.10 variant surface glycoprotein was required to generate resistant (R) clones. In addition, in this strain transcription of a gene termed SRA was detected in R clones only. We show that the ETat 1.10 expression site is the one selectively transcribed in R variants. This expression si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
128
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 331 publications
(132 citation statements)
references
References 26 publications
3
128
0
1
Order By: Relevance
“…The resulting plasmid pkD.Luc was linearized with AvrII and KpnI and transfected into 221 ES .121 tet or Δdot1b.121 tet . pRib.Luc was generated by cloning the luciferase gene between the HindIII and BamHI sites of pTSA-Rib (Xong et al, 1998), in which the tubulin 3′UTR had been replaced by the PARP 3′ region and the hygromycin resistance by puromycin resistance. The resulting plasmid was SphI linearized and transfected into 221 ES .121 tet , creating Luc rPro .221 ES .121 tet .…”
Section: Methodsmentioning
confidence: 99%
“…The resulting plasmid pkD.Luc was linearized with AvrII and KpnI and transfected into 221 ES .121 tet or Δdot1b.121 tet . pRib.Luc was generated by cloning the luciferase gene between the HindIII and BamHI sites of pTSA-Rib (Xong et al, 1998), in which the tubulin 3′UTR had been replaced by the PARP 3′ region and the hygromycin resistance by puromycin resistance. The resulting plasmid was SphI linearized and transfected into 221 ES .121 tet , creating Luc rPro .221 ES .121 tet .…”
Section: Methodsmentioning
confidence: 99%
“…The diagnostic feature of Tbr is the presence of the serum resistance associated (SRA) gene (Gibson 2005), which enables Tbr to evade lysis by the Apolipoprotein L-1 ( ApoL-1 ) in human serum (Van Xong et al 1998). Aside from this crucial functional distinction, previous studies, including most recently a kinetoplast CO1 ( Cytochrome Oxidase ) sequence and eight nuclear microsatellites of 142 isolates across Africa (Balmer et al 2011), have shown lack of differentiation between Tbb and Tbr , while finding clear genetic differences between Tbg and Tbb/Tbr (Gibson 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Reduced TLF binding/uptake operates in T. b. gambiense due to reduced expression of HpHbR and/or mutations in HpHbR [14][16]. Endosomal sequestration of APOL1 operates in T. b. rhodesiense due to the expression of a serum resistance-associated protein (SRA) related to a glycosyl-phoshatidylinositol membrane-anchored variant surface glycoprotein (VSG) [2], [17]. Expression of a VSG-related protein also confers TLF-resistance to T. b. gambiense [18], [19], but in this case the VSG-like T. b. gambiense -specific glycoprotein or TgsGP may protect cells from APOL1 by stiffening endosomal membranes rather than through direct interaction with, or sequestration of, APOL1 [19].…”
Section: Introductionmentioning
confidence: 99%